Bimodal felsic plutonism in the North Delhi fold belt, India - Khatatneh, M. K.; Pandit, M. K. (Journal of Nepal Geological Society, 1996)
The late Proterozoic rocks of the Delhi Supergroup in the northern part of the Indian shield have undergone multiphase deformation and subsequent felsic plutonism. The magmatic activity in the Ajitgarh pluton in the North Delhi Fold Belt (NDFB) is characterized by a bimodal trondhjemite-granite association. This is the first report of trondhjemite occurrence in late Proterozoic environs from this region. The bimodal character of the suite as indicated by the field disposition and petrographic characters is also confirmed by statistical and geochemical parameters. The trondhjemite and granite represent two different pulses of felsic magmatism. These two types also demonstrate a time gap of emplacement and the evolution most probably took place through distinct trondhjemitic and calc-alkaline trend.